2021
DOI: 10.3389/fcvm.2021.715258
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Fibrosis: Cellular Effectors, Molecular Pathways, and Exosomal Roles

Abstract: Cardiac fibrosis, a common pathophysiologic process in most heart diseases, refers to an excess of extracellular matrix (ECM) deposition by cardiac fibroblasts (CFs), which can lead to cardiac dysfunction and heart failure subsequently. Not only CFs but also several other cell types including macrophages and endothelial cells participate in the process of cardiac fibrosis via different molecular pathways. Exosomes, ranging in 30–150 nm of size, have been confirmed to play an essential role in cellular communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 149 publications
(60 reference statements)
1
39
0
1
Order By: Relevance
“…The proposed relationship between renalase and macrophages deserves to be discussed as a separate section, owing to a few noteworthy macrophage responses incited by renalase, particularly in light of a significant role for monocytes and macrophages as regulators of cardiac fibrosis ( 148 155 ). To date, there is substantial evidence that renalase in vivo provides several beneficial effects, such as the hindrance of total macrophage accumulation ( 10 13 , 19 , 20 , 47 , 67 , 84 , 102 ), specifically the inflammatory phenotype ( 20 , 84 ), polarizing them toward the M2 phenotype ( 84 ), and blocking inflammasome activation, and IL-1β secretion ( 10 , 47 , 67 ).…”
Section: The Renalase-dependent Signaling Of Macrophages Within the C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed relationship between renalase and macrophages deserves to be discussed as a separate section, owing to a few noteworthy macrophage responses incited by renalase, particularly in light of a significant role for monocytes and macrophages as regulators of cardiac fibrosis ( 148 155 ). To date, there is substantial evidence that renalase in vivo provides several beneficial effects, such as the hindrance of total macrophage accumulation ( 10 13 , 19 , 20 , 47 , 67 , 84 , 102 ), specifically the inflammatory phenotype ( 20 , 84 ), polarizing them toward the M2 phenotype ( 84 ), and blocking inflammasome activation, and IL-1β secretion ( 10 , 47 , 67 ).…”
Section: The Renalase-dependent Signaling Of Macrophages Within the C...mentioning
confidence: 99%
“…Moreover, possible disorganization between these macrophages’ profiles, according to some authors, represents, at least partially, an underlying mechanism of overwhelmed myocardial inflammation and subsequent cardiac fibrosis ( 1 3 , 5 , 6 , 152 – 155 ). To accomplish appropriate evolution from the stage of cardiac tissue repair to a regenerative point, cardiac macrophages most likely have to be supervised, and fine-tuned between pro-fibrotic and anti-fibrotic traits ( 6 , 7 , 151 , 153 ), particularly since macrophages are cells characterized by high plasticity ( 3 , 5 , 6 , 31 , 32 , 148 155 ), whose functions may be context-dependent (steady-state or injury). In line with that, it is confirmed that during the proliferative phase, a macrophage’s modulation aims to boost the M2-phenotype, and deplete M1-macrophages, and results in a significant lessening of interstitial cardiac fibrosis ( 3 , 5 , 6 , 154 ).…”
Section: The Renalase-dependent Signaling Of Macrophages Within the C...mentioning
confidence: 99%
“…Exosomes have a circular single-membrane structure and range between 30 and 150 nm in size. They are formed by a series of regulated processes such as endocytosis-fusion-exocytosis ( Raposo & Stoorvogel, 2013 ; Zaborowski et al, 2015 ; Nguyen et al, 2016 ; Jiang et al, 2021 ). Early endosomes are formed by invagination of the cell membrane and subsequently mature into multivesicular bodies (MVBs) ( Raposo & Stoorvogel, 2013 ; Yáñez-Mó et al, 2015 ).…”
Section: Structure and Function Of Exosomesmentioning
confidence: 99%
“…Although numerous pathogenic factors have been identified, the specific mechanisms underlying its development are unclear and require further investigation. Exosomes are small vesicles (30–150 nm in size) secreted by cells that play an essential role in intercellular communication ( Zaborowski et al, 2015 ; Jiang et al, 2021 ), mediated by a class of proteins and nucleic acids carried within the exosomes that are transported from cell to cell ( Zamani et al, 2019 ). Under disease conditions, fibroblasts, cardiomyocytes, macrophages, lymphocytes, and vascular endothelial cells communicate with each other through exosomes and their cargoes, ultimately leading to myocardial fibrosis ( Jiang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation